Copyright (and) Culture: the governance of audiovisual archives. Issue 6 (12th September 2016) - Sarikakis, Katharine; Kolokytha, Olga; Rozgonyi, Krisztina
Abstract : Purpose: This paper asks the following research question: What are the policy dynamics of copyright regulation for digital audiovisual (AV) archives in Europe and what is their potential impact? The paper aims to discuss the social relevance of archives, European cultural policies targeting operationalisation of these archives and underpinnings and sought implementation of copyright policies. Design/methodology/approach: Drawing upon three European cultural policy approaches, namely, democratisation of culture, cultural democracy and governmentalisation of culture, the discussion aims to situate current legislative attempts within digital content governance and examine policy as to its proclaimed aims of broadening access. The authors deployed macro-level legal analyses of key legislative acts of the European Union (EU) with direct relevance to the availability of and accessibility to digital historical content by European citizens. The authors juxtapose relevant cultural policy interventions with the corresponding legal rules and norms in copyright legislation. The authors evaluate the ways in which normative arguments are reflected in these acts and propose reflections on documented and possible impact. Findings: The authors argue that the EU's legal direction is characterised by uncertainty of conviction and internal tensions regarding the place of common cultural heritage in EU policy, and they present a restrictive acknowledgement of what culture and heritage policy entail and, by extension, how cultural matters should be governed. Cultural heritage AV archives are examples of digital content whose governance was almost "automatically" linked to copyright. Originality/value: The paper links copyright and cultural policy and demonstrates that although the EU cultural policy is based on access, availability and usability, copyright is unnecessarily restraining them with the improper design and implementation of exceptions and limitations. This reflects EU's focus on the single market, which, in this case, is pursued at the expense of building of a European identity with shared memories.